The evaluation of risk factors of genesis of plural caries in children with pathology of gastrointestinal tract - Luchynskyi, M. A.; Rozhko, V. I. (Journal of Education, Health and Sport, 2017)
The s<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">ubstantial risk factors<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> of development of plural caries in children with gastrointestinal diseases are <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">toxicosis of pregnancy, extragenital <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">mother <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">diseases, children<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> diseases of junior age<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">,<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">inferior feed, irregular<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> oral hygiene. The research aim was to study risk factors of genesis of plural caries in children with gastrointestinal diseases.For thedecision of aim were inspected260 children 6‒15-years-old.The result of undertaken studies: <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">a relative risk of<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">development of caries <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">at pathology<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> o<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">f<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> p<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">regnancy<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">and luingins <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">in <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">children with a plural caries<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">was<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK"> <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">in 1,4 times higher than<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">for children<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">without <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">pathology.<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">In the same time, functional<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> disorders<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK"> <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">of <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">GIT<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">,<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">oligotrophy<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">and rachitis,<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> children diseases of junior age<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK"> <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">ensure<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK"> <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">development of the<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">decompensate<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">d <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">form of caries,<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">with<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK"> <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">a relative <span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">r<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">isk,<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">in 2,25 times<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">higher than for children<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">without mentioned<span style="font-size: 12pt; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">pathologies.